QUALITY CONTROL AND PRODUCTIVITY OF METAL CRAFT PRODUCTS IN PASIR MUKTI VILLAGE, CITEUREP DISTRICT, BOGOR REGENCY - Shinta Aminda, Renea; Suharti, Titing; Kartika Rinda, Rachmatullaily; Surend Mahmud, Khalishah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Metal products are one of the superior products of Bogor Regency, which is located in Pasirmukti Village, Sukahati, and Tarikolot, Citeureup District. The local government of Bogor Regency has made the icons in these villages a thematic village that will be used as an integrated training center for marketing the products of the metal and body industry. The area of ​​Citereup District is because the area has also produced metal industries since the 1980s, and has survived to this day, Micro, Small and Medium Enterprises (MSMEs) are the main supporter of the economy of the residents of Citeureup District. "The majority of the population is SMEs, there are few civil servants and farmers, and some work as service providers", the name "Kampung Kaleng" was given because all the craftsmen in Kampung Dukuh make products made from cans. “Kaleng Kaleng officially existed in 2012, but the craftsmen themselves have existed for a long time and have been passed down from generation to generation.” This Kampung Kaleng resident has marketed his products to other islands such as Kalimantan, Makassar, and other areas in Indonesia through online media and exhibitions he participated in. Previously, craftsmen were only able to sell their products to the Greater Jakarta area. The manufacturing process from raw materials to finished products is carried out directly by the residents of Kampung Dukuh. Raw materials are obtained from existing distributors in the Citeureup area itself. Product prices in Kampung Kaleng are quite diverse depending on the type of goods and their size. The range starts from IDR 15 thousand for a can of mini crackers to IDR 700 thousand for the price of an oven. "The turnover for craftsmen is around IDR 500,000 thousand to IDR 1,000,000 per day". The profit that the craftsmen take is about 10% to 20% of the sales turnover. The competence of the metal industry IKM Manager in Bogor Regency is still low. The problem of competence and performance of human resources related to the opportunity for industrial development in producing standardized product quality is a problem for the metal industry SMEs. The improvement strategy that can be carried out is conducting training and continuous development regarding knowledge, certified skills, and motives supported by the Bogor Regency Cooperatives and SMEs Office as well as government regulations that support IKM in increasing competitiveness which has an impact on sustainable business. Small and medium industries for the metal industry are centered in Citeureup District with a total of 194 business units spread across several villages. SMEs have been proven to make a significant positive contribution to efforts to overcome economic problems. The metal industry can also create jobs and reduce unemployment, expand employment and provide economic services. However, in reality, there is a gap faced by metal SMEs today. The purpose of this community service is to find out how the production function of metal crafts is in controlling product quality, secondly to determine the effect of Physical Facilities in Metal Workshops on product quality control, thirdly to find out how to Inspect Product Quality Control, and fourthly how to influence the production function and physical facilities of the workshop. to control checks on product quality.